Hydrological behaviour of a small catchment in the dehesa landuse system (Extremadura, SW Spain) - Ceballos, Antonio; Schnabel, Susanne (Journal of Hydrology, 1998)
Investigations of the hydrological processes operating in a small experimental catchment representative of the dehesa ecosystem were carried out. The dehesa constitutes a system of agro-silvo-pastoral landuse, which is characterized by a Mediterranean, semi-arid climate. The study includes an analysis of the relationships between rainfall, soil water content and discharge, as well as the establishment of the annual water budget. The results demonstrate a complex hydrological response. The relationships between the factors involved and the operating processes are difﬁcult to explain because of the decisive role played by the valley bottoms. These areas typically possess a sediment ﬁll, and contrast with the shallow soils developed on the hillslopes. Genesis and quantity of runoff (Hortonian or saturation) measured at the outlet depend on the antecedent moisture conditions of the valley bottoms because of their water-retention capacity. Annual runoff coefﬁcients are similar to those reported from other semi-arid areas. The analysis of the annual water budget shows that rainfall is positively related with both actual evapotranspiration and discharge
Keywords: Dehesa; Runoff–rainfall relationship; Semi-arid areas; Small catchment; Water budget